Phase equilibrium modelling of Palaeoproterozoic ultrahigh-temperature sapphirine granulite from the Inner Mongolia Suture Zone, North China Craton: implications for counterclockwise P-T path - Shimizu, Hisako; Tsunogae, Toshiaki; Santosh, M.; Liu, S. J.; Li, J. H. (Geological Journal, 2013)
We report new petrological data on the sapphirine granulite from Tuguiwula in the Inner Mongolia Suture Zone in the North China Craton which further confirm extreme crustal metamorphism associated with collisional orogeny. The peak metamorphic conditions of the rock have been estimated by sapphirine+quartz assemblage at T>950 degrees C and P>7.5kbar (M1) based on mineral equilibrium modelling in the NCKFMASHTO system. These conditions are slightly lower than those reported in previous studies (similar to 1050 degrees C and 10.5kbar) due to the consideration of Fe2O3 content in the sapphirine granulite in this study, although we confirm a peak ultrahigh-temperature metamorphism in this region. The peak event was followed by a cordierite-forming retrograde event (M2), and biotite-forming retrograde stage (M3) which are constrained in the P-T pseudosection by the stability of cordierite (<7.5kbar) and biotite+sillimanite+K-feldspar (<890 degrees C). Combining the results of this study and the petrological observations of spinel+quartz assemblage formed prior to sapphirine+quartz, and orthopyroxene+sillimanite+quartz assemblage after sapphirine+quartz reported in previous studies, a counterclockwise P-T history for these rocks is further confirmed, reflecting heat input into the lower crust from asthenospheric upwelling and underplating associated with the Palaeoproterozoic collisional orogeny in the North China Craton. Copyright (c) 2013 John Wiley & Sons, Ltd. Geosciences, Multidisciplinary SCI(E) 3 ARTICLE 5,SI 456-466 48